Origin, charging, and mixing of crude oils in the Tahe oilfield, Tarim Basin, China. (June 2017) - Zhan, Zhao-Wen; Zou, Yan-Rong; Pan, Changchun; Sun, Jia-Nan; Lin, Xiao-Hui; Peng, Ping'an
Highlights: The crude oils are mixtures of different maturity oils generated from two source rocks. The number, contributions and compositions of endmembers were estimated using chemometrics. The general oil charge orientations were from south to north and east to west. A model of petroleum charge, biodegradation and mixing was proposed. Abstract: Forty-eight crude oil samples collected from different reservoirs in the Tahe oilfield of the Tarim Basin were investigated. Based on geochemical characteristics, it is concluded that the oil samples originated from multiple marine source rocks deposited in various sedimentary environments and subsequently altered by different levels of thermal maturation. These mixtures were de-convoluted to three endmember oils (EM1, EM2 and EM3) by alternating least squares regression using 38 concentration parameters. EM1 is the minimum contributor with an average of 13%, while EM2 and EM3 are the main contributors to the mixtures with averages of 52% and 35%, respectively. EM1 oil originated from Cambrian–Lower Ordovician source rocks in the early to peak oil window and subsequently experienced two phases of mixing and biodegradation. EM2 and EM3 oils originated from Middle–Upper Ordovician source rocks, but EM2 was generated at lower thermal maturity than EM3. The EM2 oil underwent two phases of mixing and one stage biodegradation, while the EM3 oil mixed with previous existing mixtures in the reservoirs. The final mixtures that might be affected by secondary processes, such as evaporative fractionation, are currently produced from the Tahe oilfield. The general orientation of oil filling was from south to north and east to west based on variations in the relative contributions of EMs, and the total concentrations of dibenzothiophenes and dibenzofurans in the oils. Considering the histories of sedimentary tectonic evolution, hydrocarbon generation and expulsion, and the de-convolution results, a model of three stages of oil charge and two phases of mixing and biodegradation was established for the Tahe oilfield oils.